2007
DOI: 10.1590/s1517-83822007000100020
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic meningitis by echovirus 30 in São Paulo state, Brazil

Abstract: The objective of this study was to identify and characterize the immunological and molecular aspects of Human Enterovirus (HEV) associated with aseptic meningitis cases in São Paulo State, Brazil. Clinical samples (cerebrospinal fluid CSF, stool and sera) were analyzed from 21 viral meningitis suspected cases collected in the period from 1998 to 1999. The isolated virus were identified as belonging to Enterovirus genus and specifically to echovirus serotype 30 (EV-30), using immunological techniques as Indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…These viruses are transmitted via oral-fecal route and mostly seen in fall and summer at temperate areas (4). Echovirus 30 as a member of enteroviruses was reported from some countries such as Kuwait, Turkey, Brazil, and Korea (2,(5)(6)(7). Cell culture was the gold standard and classical diagnostic method for detection and isolation of enteroviruses but as this method is very time consuming and needs much facilities, after the advent of molecular techniques such as PCR most studies are performed based on these techniques (8).…”
Section: Introductionmentioning
confidence: 99%
“…These viruses are transmitted via oral-fecal route and mostly seen in fall and summer at temperate areas (4). Echovirus 30 as a member of enteroviruses was reported from some countries such as Kuwait, Turkey, Brazil, and Korea (2,(5)(6)(7). Cell culture was the gold standard and classical diagnostic method for detection and isolation of enteroviruses but as this method is very time consuming and needs much facilities, after the advent of molecular techniques such as PCR most studies are performed based on these techniques (8).…”
Section: Introductionmentioning
confidence: 99%
“…E-9 was the predominant HEV serotype identified in the eastern United States in 2003 (5), and E-9 and E-30 have been frequently associated with AM outbreaks (4). In Brazil, E-30 has been the most prevalent etiological agent of viral meningitis, causing both outbreaks and sporadic cases (7,14). …”
mentioning
confidence: 99%
“…Recent Brazilian epidemiological studies regarding AM have identified E-1, E-4, E-9, E-13, E-18, E-25 and E-30, CV-B2, CV-B3, CV-B5, CV-B6, and HEV-71 as the most common serotypes (7, 12, 14, 27). In a study conducted between 1998 and 2003, Santos et al .…”
mentioning
confidence: 99%
“…[1][2][3][4][5] No Brasil, os enterovírus também são os principais responsáveis pela meningite viral. 6 O comportamento epidêmico não é só observado no Recife, senão também em outras cidades brasileiras 7,[16][17][18][19][20] e países do mundo, 3,5,[8][9][10][11][12] incluindo os mais desenvolvidos. As duas epidemias detectadas foram diferentes, tanto no que se refere à magnitude quanto no delineamento das curvas.…”
Section: Mês/anounclassified
“…6,7,17 A segunda epidemia, cujo agente causal não foi identificado, apresentou maior número de casos que a anterior e risco de adoecimento 7,66 vezes maior do que no período endêmico correspondente. Nas duas epidemias, os casos ocorreram em todas as regiões da cidade, com maior quantidade de bairros atingidos e maior frequência de casos por bairro, em relação aos períodos endêmicos.…”
Section: Mês/anounclassified